A new technique to estimate percentage decolorization of synthetic dyes on solid media by extracellular laccase from white-rot fungus. Issue 1 (2nd January 2023) - Shah, Harmen; Yusof, Faridah; Alam, Md Zahangir
Abstract: The enormous colored effluent discharges due to increased usage of synthetic dyes in textile and other chemical industries pollute both freshwater and marine reservoirs and cause ecotoxicity and serious health problems. This issue needs to be addressed skillfully and demands an ecofriendly and economically feasible technique. Pertaining to this, the current study was focused on the use of a white rot fungus, Resinicium bicolor to decolorize and degrade a recalcitrant dye, Congo red (CR) through its extracellular laccase enzyme secreted by mycelia. This work was also intended to develop a simple mathematical formula to calculate decolorization (%) of various dye categories usually tested on the solid medium plate involving different white rot fungi. The fungus was grown on malt extract agar (MEA) plate containing media supplemented with CR, 1% (g/l) to check the extent of decolorization and hence efficacy of Resinicium bicolor laccase at an interval of 24 hours (hrs). Decolorization (%) was determined by a formula derived from 'Plate Volume Method' (PVM). The maximum decolorization achieved on solid medium was 97.79% and 96.79% in liquid culture medium by the end of 96 hrs without the involvement of any chemical mediators which are generally toxic and expensive. Efficient decolorization achieved in the liquid medium validated the accuracy of 'PVM'.